Multiple element of miniaturized printed log-periodic second series koch dipole array antenna for wideband chipless RFID tag reader - Mohd Ezwan Bin Jalil; Mohamad Kamal A. Rahim; Noor Asmawati Samsuri; Sunti Tuntrakool (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper aims to produce a low profile, wideband, and high gain antenna for chipless RFID tag readers. A miniaturized and wideband printed Log-periodic second series koch dipole array (LPSSKDA) with eleven elements operating over 0.8 GHz-3.2 GHz is designed using the FR4 board. The single LPSSKDA antenna, which acts as the chipless RFID reader antenna having gain between 5.2 and 6.1 dBi and frequency range from 1-3 GHz. A double element of the LPSSKDA antenna is proposed for improving the antenna gain to 6.9-7.9 dBi over the frequency range. The antenna is fabricated to validate the simulation and measurement results in terms of reflection coefficient, radiation pattern, and surface current distribution.